Hematology Profile and Liver Histopathology in Escherichia coli Infected Layers Treated with Combination of Phyllanthus ( Phyllanthus niruri L. ) and Turmeric ( Curcuma domestica ) - Sri Hartati; Tri Untari; Bambang Sutrisno; Ida Fitriana (Jurnal Sain Veteriner, 2021)
Colibacillosis a disease that can cause considerable economic loss, remains an important health problem. Phyllanthus (Phyllanthus niruri L) and turmeric (Curcuma domestica) are herbs that can be used as immunomodulators. This study was aimed to determine the level of safety of the combination of phyllanthus and turmeric on hematology profile and liver histopathology of layers with colibacillosis. The layers were assigned to the following of 5 groups: a) colibacillosis group without treatment, b) colibacillosis group with 500 mg/kg BW of phyllanthus, c) colibacillosis group with 300 mg/kg BW of turmeric, d) colibacillosis group with phyllanthus and turmeric combination (1:1), e) colibacillosis group with combination of phyllanthus and turmeric (1:2) . After 21 days of treatment, blood and liver sample were collected. The hematological profile (hemoglobin, hematocrit, erythrocyte and leukocyte counts) and liver histology were examined. The result were analyzed statistically by one-way ANOVA. The group that received phyllanthus had higher levels of hemoglobine, haematocrit and erythrocytes than the control group. However, no significant differences were found for the overall groups. Treatment with the combination of turmeric and phyllanthus for 21 days did not cause changes in the hematological profiles or liver histology, and therefor this herbal combination can be used as an alternative therapy for colibacillosis in layers.